Prediction of Refractive Error Based on Ultrawide Field Images With Deep Learning Models in Myopia Patients - Yang, Danjuan; Li, Meiyan; Li, Weizhen; Wang, Yunzhe; Niu, Lingling; Shen, Yang; Zhang, Xiaoyu; Fu, Bo; Zhou, Xingtao (Frontiers in Medicine, 2022)
Abstract Summary: Ultrawide field fundus images could be applied in deep learning models to predict the refractive error of myopic patients. The predicted error was related to the older age and greater spherical power. Purpose: To explore the possibility of predicting the refractive error of myopic patients by applying deep learning models trained with ultrawide field (UWF) images. Methods:987 UWF fundus images were collected from left eyes of enrolled myopia patients of Eye and ENT Hospital, Fudan University from November 2015 to January 2019. The fundus images were all captured with Optomap Daytona, a 200-degree UWF imaging device. Three deep learning models (ResNet-50, Inception-v3, Inception-ResNet-v2) were trained with the UWF images for predicting refractive error. 133 UWF fundus images were collected after January 2021 as the external validation set. The predicted refractive error was compared with the “true value” measured by subjective refraction. Mean absolute error (MAE), mean absolute percentage error (MAPE) and coefficient (R2) value were calculated in the test set. The Spearman rank correlation test was applied for univariate analysis and multivariate linear regression analysis on variables affecting MAE. The weighted heat map was generated by averaging the predicted weight of each pixel. Results: ResNet-50, Inception-v3 and Inception-ResNet-v2 models trained with the UWF images for refractive error prediction with R2 of 0.9562, 0.9555, 0.9563 and MAE of 1.72(95%CI: 1.62-1.82), 1.75(95%CI: 1.65-1.86) and 1.76(95%CI: 1.66-1.86), respectively. 29.95%, 31.47% and 29.44% of the test set were within the predictive error of 0.75D in the three models. 64.97%, 64.97%, and 64.47% was within 2.00D predictive error. The predicted MAE was related to older age(P＜0.01) and greater spherical power(P＜0.01). The optic papilla and macular region had significant predictive power in the weighted heat map. Conclusions: It was feasible to predict refractive error in myopic patients with deep learning models trained by UWF images with the accuracy to be improved.